IDEATIONAL MEANING ANALYSIS IN ANALYTICAL EXPOSITION TEXT WRITTEN BY THE ELEVENTH GRADERS OF SMA NEGERI 1 MAGELANG IN THE ACADEMIC YEAR 2018/2019 - Chanifah Chanifah (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
In this paper, the writer focuses on the ideational meaning in the eleventh graders composition of analytical exposition text. The objectives of this study are to know the process types used and to know the dominant process type used in analytical exposition text written by the eleventh graders of SMA Negeri 1 Magelang in the academic year 2018/2019. The type of this study is qualitative, so the writer analyzes the data through descriptive qualitative. The subject of this study was the eleventh graders’ analytical exposition text in XI Social 2 of SMA Negeri 1 Magelang in the academic year 2018/2019. The writer took 12 analytical exposition texts which were analyzed and collected by documentary technique. The result revealed that the total numbers of processes are contributed into six process types. Those are material processes, mental processes, behavioral process, verbal processes, relational processes and existential processes. Thus, the dominant process type is relational process which are divided into attributive processes and identifying processes. Students mostly used relational processes to give their idea about phenomenon discussed in their analytical exposition texts. Finally, the writer suggests the teacher to master ideational meaning and explain more about the lexicogrammatical feature used in analytical exposition text so that the students can compose qualified writing.